A speech therapy treatment protocol for exercise induced laryngeal obstruction - Karlsen, Tom; Vreim, Kristine; Røksund, Ola D.; Vollsæter, Maria; Muralitharan, Praveen; Ellingsen, Thor Andre; Heimdal, John-Helge; Halvorsen, Thomas; Clemm, Hege (Frontiers in Pediatrics, 2024)
Background: Exercise induced laryngeal obstruction (EILO) is a common cause of exertional breathing problems in young individuals, relevant to 5-7% of young people. It is caused by paradoxical inspiratory adduction of laryngeal structures and diagnosed by continuous visualization of the larynx during high intensity exercise. Empirical data suggest that EILO consists of different subtypes that require different therapeutic approaches. Currently applied treatment approaches do not rest on randomized controlled trials (RCTs), and thus evidencebased guidelines cannot be established. This protocol describes the speech therapy treatment approach which is applied to EILO patients in a large prospective RCT called HelpILO.Haukeland University Hospital are randomized into four treatment arms. Speech therapy is represented in two of these, provided in a structured manner based on general speech therapy principles and abdominal breathing, combined with experience obtained with these patients at our hospital during the last decades. The main outcome measure of HelpILO is changes of laryngoscopically visualized laryngeal adduction, rated at peak exercise before versus after interventions, using a validated scoring system.